ECONOMIC ASSESSMENT OF FUNCTIONING OF GRAIN FARMS IN THE CONDITION OF COMBINATION OF SMALL AND MEDIUM AGRIBUSINESS - O. V. Sidorenko; I. V. Iliena (Зерновое хозяйство России, 2018)
One of the most important priorities of the governmental economic strategy is to form and develop multi structural (mixed) economy as a basis of stable progress of agricultural territories and stable condition of the countryside. Thus, the study of the experience of some regions, enterprises, analysis of the factors and development of practical recommendations is of great importance. The purpose of the study is to monitor of functioning of agricultural enterprises being a part of regional grain productive subcomplex in the in the condition of combination of small and medium agribusiness. In the work the analysis of financial and economic activity of grain farms of Orlov region has been conducted with the help of scientific, economic and statistical methods of study. Features of agricultural production have been revealed taking into consideration sizes and specialization of the enterprises. A complex of enterprises which shows interconnection of productive efficiency with amount of expenditures and subsidies per hectare of grain crops, has been considered. It has been established small and medium agro enterprises develop more efficient but meet preconditions of financial deterioration which can lead to bankruptcy. The conclusion has been made that mixed economy is a principal position of development of domestic grain productive subcomplex nowadays.  The results of economic monitoring have been used when making practical recommendations how to increase profitability of agricultural enterprises of Orlov region. The significance of the study is essential under conditions of implementing Governmental Program “Development of Agriculture and Regulation of Agricultural Markets, Raw material and Food during 2013-2020”. The most important tasks of the program are to give support to small farms and to increase profitability in agriculture.